Cartographic analysis of enterprise risk management research: A bibliometric study using Scopus data (2014–2024) - Armin, Rini; Setiawan, Rahmat; Windijarto, Windijarto (Edelweiss Applied Science and Technology, 2025)
Enterprise Risk Management (ERM) has evolved into an increasingly important strategic field as organizations enhance their capacity to systematically manage uncertainty. This study aims to map the intellectual and thematic development of ERM through cartographic and bibliometric analysis of 261 documents indexed in Scopus during the period 2014–2024. By integrating the VOSviewer and Biblioshiny tools, the methodological approach includes co-authorship analysis, co-emergence, co-citations, bibliographic coupling, and thematic trend identification. The results reveal the dominant contributions of authors such as Moloi T. and Fraser J., as well as the most prolific journals and countries, with Indonesia emerging as a major actor in the Southeast Asian region. Thematic mapping indicates a shift towards a more empirical approach, with a primary focus on risk assessment and the integration of ERM into organizational strategy. The study concludes that ERM is evolving in a more structured and collaborative direction, highlighting the need for cross-disciplinary and cross-country exploration. The practical implications of these findings provide data-driven guidance for researchers, institutions, and policymakers in aligning the ERM research and policy agenda with changing global dynamics.